Adaptive Sleep Scheduling for Health Monitoring System Based on the IEEE 802.15.4 Standard - Fahmi, Nurul; Al Rasyid, M. Udin Harun; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
In the recent years, Wireless Sensor Networks (WSNs) have become a very popular technology for research in various fields. One of the technologies which is developed using WSN is environmental health monitoring. However, there is a problem when we want to optimize the performance of the environmental health monitoring such as the limitation of the energy. In this paper, we proposed a method for the environmental health monitoring using the fuzzy logic approach according to the environmental health conditions. We use that condition to determine the sleep time in the system based on IEEE 802.15.4 standard protocol. The main purpose of this method is to extend the life and minimize the energy consumption of the battery. We implemented this system in the real hardware test-bed using temperature, humidity, CO and CO2 sensors. We compared the performance without sleep scheduling, with sleep scheduling and adaptive sleep scheduling. The power consumption spent during the process of testing without sleep scheduling is 52%, for the sleep scheduling is 13%, while using the adaptive sleep scheduling is around 7%. The users also can monitor the health condition via mobile phone or web-based application, in real-time anywhere and anytime.